Pengaruh Model Pembelajaran Quantum Learning Terhadap Kemampuan Komunikasi Matematis Siswa Kelas XI SMA Negeri 1 Sosa - Hasibuan, Sundut Azhari; Hasibuan, Septiana; Siregar, Syarimah (Journal of Information System and Education Development, 2025)
This study aims to determine whether the use of the Quantum Learning model affects the mathematical communication skills of Class XI students at SMA Negeri 1 Sosa for the Academic Year 2024/2025. This research is a quasi-experimental study with the population being the Class XI students of SMA Negeri 1 Sosa for the Academic Year 2024/2025. The class is divided into two groups, one as the experimental class and one as the control class. The experimental class is taught mathematics using the Quantum Learning model and the control class is taught using the conventional learning model. The research instrument consists of a test of students' mathematical communication skills which has been tested for validity, reliability, difficulty index, and discrimination power of the questions. The results of the testing concluded that the mathematical communication ability test for students is suitable for use. The hypothesis testing results showed that the t-value with equal variances assumed is 1.875 while the t-table value for df 52 is 1.675. Therefore, the t-value > t-table indicates that H1 is accepted. According to the research hypothesis in H1, there is an effect of the quantum learning model on students' mathematical communication abilities in class XI at SMA Negeri 1 Sosa for the academic year 2024/2025. Each indicator has the highest mastery percentage in the experimental class (quantum learning) compared to the control class (conventional). The best indicator of mathematical communication ability in the experimental class is indicator 3 (Ability to understand and evaluate mathematical ideas). The mastery percentage for the indicator in the experimental class is 85%, while in the control class it is 83.80%.